Aquaculture engineering - Lekang, Odd-Ivar (Wiley-Blackwell, 2013)
"As aquaculture continues to grow at a rapid pace, understanding the engineering behind aquatic production facilities is of increasing importance for all those working in the industry. Aquaculture engineering requires knowledge of the many general aspects of engineering such as material technology, building design and construction, mechanical engineering, and environmental engineering. In comprehensive book now in its second edition, author Odd-Ivar Lekang introduces these principles and demonstrates how such technical knowledge can be applied to aquaculture systems"-- Provided by publisher